Development of Game Case Media to Increase Students' Interest in Learning Mathematics - Dita Oktavihari; Nanang Priatna (MEJ (Mathematics Education Journal), 2021)
Development research aims to develop game case media in order to increase student interest in the problem-solving-based mathematics learning process during the covid-19 pandemic. The method used is R & D (Research and Development) with the ADDIE model. The research instrument used was a validation sheet and a questionnaire sheet. The data analysis used is descriptive quantitative to process data in the form of scores from validator assessments and student responses and uses purposive sampling technique in taking samples. The validation results obtained a score of 4 for the assessment of the material aspect which was categorized as good and a score of 4.56 for the assessment of the material aspect which was categorized as very good. Based on the validation results, the game case learning media can be tested in the implementation phase. Based on the results of the student response questionnaire obtained 75.25%. This resulted in learning media in the form of game cases to be well received. These results indicate that this game case media can be developed in order to increase students' interest in learning in the problem-solving-based mathematics learning process during the covid-19 pandemic.